2020
DOI: 10.1177/0954405420901420
|View full text |Cite
|
Sign up to set email alerts
|

Hole quality and tool wear when dry drilling of a new developed metal/composite co-cured material

Abstract: The new developed metal/composite co-cured material composed of carbon fiber–reinforced plastic and Al phases has been increasingly applied for manufacturing of attitude control flywheel in aerospace industry. However, drilling of co-cured material is still a challenging task to produce holes with high quality and low cost in the assembly chain and dynamic balance debugging of attitude control flywheel. In other words, the relevant mechanisms and experimental findings involved in the drilling process of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…6,8,20 A machined multidirectional composite surface has been shown to have a non-homogeneous surface: this has been shown in the literature using various methods, including computed tomography (CT), scanning electron microscopy (SEM) and optical focus variation measurement techniques. 11,12,16,21 Other researchers have used advanced techniques to assess sub surface damage including terahertz imaging and epiflourescent microscopy. 22,23 Wang et al 24 have used a new image subtraction method to quantify the extent of delaminated fibres on an edge trimmed edge using an image subtraction method.…”
Section: Review Of State-of-the-art Measurement Methods and Statisticmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,20 A machined multidirectional composite surface has been shown to have a non-homogeneous surface: this has been shown in the literature using various methods, including computed tomography (CT), scanning electron microscopy (SEM) and optical focus variation measurement techniques. 11,12,16,21 Other researchers have used advanced techniques to assess sub surface damage including terahertz imaging and epiflourescent microscopy. 22,23 Wang et al 24 have used a new image subtraction method to quantify the extent of delaminated fibres on an edge trimmed edge using an image subtraction method.…”
Section: Review Of State-of-the-art Measurement Methods and Statisticmentioning
confidence: 99%
“…Specifically, in composite machining, it has been shown that ply orientation will significantly dictate the machined surface topography, cutting mechanism and defect types. 10,11 A representation of the different material cutting mechanisms in relation to fibre orientation for a fibrous composite machining process is shown in Figure 1. When this diagram is extrapolated to a multidirectional edge trimmed surface it can then be inferred that there will be a through thickness variation in ply by ply cutting mechanism and ply-induced machining defects, which has been verified by the literature.…”
Section: Introductionmentioning
confidence: 99%
“…), and drilling parameters (e.g, feed rate, cutting speed, etc.). 3134 Choosing the right parameters is crucial for improving the process efficiency of metal matrix composites. 35…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used machining technologies include turning [1,2], milling [3,4] and drilling or boring [5,6]. The aim is to achieve the desired quality of the machined surface with dimensional accuracy and surface roughness [7,8].…”
Section: Introductionmentioning
confidence: 99%